Justifying limitations on the freedom of expression - Gunatillake, Gehan (Human rights review, 2021)
The freedom of expression is vital to our ability to convey opinions, convictions, and beliefs, and to meaningfully participate in democracy. The state may, however, ‘limit’ the freedom of expression on certain grounds, such as national security, public order, public health, and public morals. Examples from around the world show that the freedom of individuals to express their opinions, convictions, and beliefs is often imperilled when states are not required to meet a substantial justificatory burden when limiting such freedom. This article critiques one of the common justificatory approaches employed in a number of jurisdictions to frame the state’s burden to justify limitations on the freedom of expression—the proportionality test. It presents a case for an alternative approach that builds on the merits and addresses some of the weaknesses of a typical proportionality test. This alternative may be called a ‘duty-based’ justificatory approach because it requires the state to demonstrate—through the presentation of publicly justifiable reasons—that the individual concerned owes others a duty of justice to refrain from the expressive conduct in question. The article explains how this approach is more normatively compelling than a typical proportionality test. It also illustrates how such an approach can better constrain the state’s ability to advance majoritarian interests or offload its positive obligations by limiting the freedom of expression of minorities and dissenting voices.